THE ROLE OF COGNITIVE AND SOCIAL SKILLS IN TEACHERS’ SELF-REGULATION - Gurbanova Fuad Qizi, Aygun; Kosayeva Vasif Qizi, Aytekin (Health and Society, 2025)
This article examines the impact of cognitive and social skills on teachers’ self-regulation, particularly in the context of job stress and emotional control. It highlights the significance of self-determination, self-improvement, and self-actualization in pedagogical education. The findings suggest that enhancing teachers’ cognitive and emotional competencies can mitigate job-related stress and improve teaching effectiveness.